The sea lamprey meiotic map improves resolution of ancient vertebrate genome duplications - Smith, Jeramiah J.; Keinath, Melissa C.

(untitled) (Genome Research, 2015)
It is generally accepted that many genes present in vertebrate genomes owe their origin to two whole-genome duplications that occurred deep in the ancestry of the vertebrate lineage. However, details regarding the timing and outcome of these duplications are not well resolved. We present high-density meiotic and comparative genomic maps for the sea lamprey (Petromyzon marinus), a representative of an ancient lineage that diverged from all other vertebrates ∼550 million years ago. Linkage analyses yielded a total of 95 linkage groups, similar to the estimated number of germline chromosomes (1n ∼ 99), spanning a total of 5570.25 cM. Comparative mapping data yield strong support for the hypothesis that a single whole-genome duplication occurred in the basal vertebrate lineage, but do not strongly support a hypothetical second event. Rather, these comparative maps reveal several evolutionarily independent segmental duplications occurring over the last 600+ million years of chordate evolution. This refined history of vertebrate genome duplication should permit more precise investigations of vertebrate evolution.